Strauss the king of 3/4 quarter time - Devine, David; Mozer, Richard; Matthews, Marlene; Hood, Kit.; Riley, Michael, 1962-; Senft, Derek; Trotter, Kate.; Frappier, Jill.; Haworth, Peter James; Richings, Julian, 1955-; McEwan, Hamish; Peloso, Glen.; et al. (Toronto, Ont., Canada : Devine Entertainment, 2002)
Haunted by the constant pressure to outdo himself with each new composition, composer Johann Strauss, Jr., meets Nicholas, a humble stable boy who fears his brutal stepfather. To their surprise, the composer and the boy discover the healing bond of trust and embark on a collaboration that will be music to the world's ears. Set in 1868, Vienna.
Special features: The filming of Strauss; The life and times of Johann Strauss, Jr.; Strauss, soundtrack; Cast of characters; Photo gallery.
DVD; Dolby digital stereo.
English, Spanish, and French; closed captioned.
Michael Riley, Derek Senft, Kate Trotter, Jill Frappier, Peter James Haworth, Julian Richings, Hamish McEwan, Glen Peloso, Linda Sorensen, Eugene Lipinski.
Director of photography, Sean Valentini ; editor, Michael Pacek ; music by Johann Strauss, Jr.
Filmed in Moravia, Czech Republic.
Originally produced for television in 1995.
Keywords: Strauss, Johann, -- 1825-1899 -- Juvenile drama; Composers -- Austria -- Juvenile drama; Made-for-TV movies; Children's films; Feature films; Fiction films; Video recordings for the hearing impaired